1994
DOI: 10.1080/09064709409410892
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ash Content on the Nutritive Value of Meat and Bone Meal for Growing Pigs

Abstract: The effcct of ash content on the nutritive value of meat and bone meal for growing pigs. Accepted October 25, 1993. Acta Agric. Scand., Sect. A, Animal Sci. 41: 152-159, 1991. 0 Acta Agric. Scand. 1994.A balance experiment was conducted with 9 barrows at live weight from 25 to 75 kg. The experiment had a 9 x 6 cyclic change-over design and the treatments were arranged factorially. The factors were three protein sources: soya bean meal (SBM), low ash meat and bone meal [MBL, 208 g ash/kg dry matter (DM)], and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…Soft offal protein appears to be more susceptible to heat damage than that of bones and other structural tissues and perhaps different processing conditions should be applied to different raw materials. This is consistent with our previous conclusions (Partanen 1994), where significantly higher nitrogen retention was observed when pigs were fed diets with meat and bone meal of high (319 g/kg) compared to low ash content (204 g/kg). Haugen et al (1985) have also reported that ileal digestibility of soft offal was reduced by increasing processing temperature, while that of hard structural offal was not affected by higher temperatures.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Soft offal protein appears to be more susceptible to heat damage than that of bones and other structural tissues and perhaps different processing conditions should be applied to different raw materials. This is consistent with our previous conclusions (Partanen 1994), where significantly higher nitrogen retention was observed when pigs were fed diets with meat and bone meal of high (319 g/kg) compared to low ash content (204 g/kg). Haugen et al (1985) have also reported that ileal digestibility of soft offal was reduced by increasing processing temperature, while that of hard structural offal was not affected by higher temperatures.…”
Section: Discussionsupporting
confidence: 93%
“…However, the high dietary mineral content may have a negative influence on the digestibility of fat and, therefore, the energy value of the diet (Jprgensen et al 1992). The lower digestibility of CF observed in MH diets compared with ML diets is in agreement with earlier results, which demonstrated that in meat and bone meals, faecal CF digestibility decreases with increasing meal ash content (Just et al 1982, Partanen 1994. The improved faecal digestibility of nutrients with increasing live weight is in agreement with earlier findings (Roth and Kirchgessner 1984).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations